Human Resources Implementation Using the McKinsey 7S Method for Business Startup: Duck Nugget Frozen Food - Ryan Perdana Putra; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Rhian Indradewa (Penerbit Kemala Indonesia, 2019)
The purpose of Nugget Duck-Duckan business plan is a company manufactures processed